Sequence variations of the partially dominant DELLA gene Rht-B1c in wheat and their functional impacts - Wen, Wen (Journal of experimental botany, 2013)
Rht-B1c, allelic to the DELLA protein-encoding gene Rht-B1a, is a natural mutation documented in common wheat (Triticum aestivum). It confers variation to a number of traits related to cell and plant morphology, seed dormancy, and photosynthesis. The present study was conducted to examine the sequence variations of Rht-B1c and their functional impacts. The results showed that Rht-B1c was partially dominant or co-dominant for plant height, and exhibited an increased dwarfing effect. At the sequence level, Rht-B1c differed from Rht-B1a by one 2kb Veju retrotransposon insertion, three coding region single nucleotide polymorphisms (SNPs), one 197bp insertion, and four SNPs in the 1kb upstream sequence. Haplotype investigations, association analyses, transient expression assays, and expression profiling showed that the Veju insertion was primarily responsible for the extreme dwarfing effect. It was found that the Veju insertion changed processing of the Rht-B1c transcripts and resulted in DELLA motif primary structure disruption. Expression assays showed that Rht-B1c caused reduction of total Rht-1 transcript levels, and up-regulation of GATA-like transcription factors and genes positively regulated by these factors, suggesting that one way in which Rht-1 proteins affect plant growth and development is through GATA-like transcription factor regulation